2018
DOI: 10.1093/advances/nmx003
|View full text |Cite
|
Sign up to set email alerts
|

Snacking Recommendations Worldwide: A Scoping Review

Abstract: Across the globe, dietary habits include the consumption of foods and drinks between main meals. Although often described as "snacks" or "snacking," there is no scientific consensus of what constitutes a snack, either as an eating occasion or as a snack food. Nonetheless, food-based dietary guidelines, compiled at national or regional levels by governments, learned societies, and health organizations, frequently refer to snacking habits and desirable or undesirable snack food choices. This review aims to provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 42 publications
3
55
0
Order By: Relevance
“…As for SSB and HSF we suggest limiting their consumption according to individual country guidelines. However, we suggest promoting their exchange in favor of a higher consumption of healthy foods, since this practice has been more effective for the general population [48].…”
Section: Discussionmentioning
confidence: 99%
“…As for SSB and HSF we suggest limiting their consumption according to individual country guidelines. However, we suggest promoting their exchange in favor of a higher consumption of healthy foods, since this practice has been more effective for the general population [48].…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the role that snacking plays in the diet quality of young children is critical given that roughly one out of every four calories consumed by US preschool-aged children are currently eaten outside of meals [3]. A recent review of snacking recommendations from 49 countries and 7 global/regional organizations worldwide, revealed that the most frequent rationale given in support of snacking was the potential value for energy and/or nutrient intakes [4]. This possibility has remained largely speculative where young children are concerned given that empirical inquiry to date has been limited and primarily descriptive [3].…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, snacking provided 26–27% of daily energy among US children aged two to five years [3]. Given its central contribution to daily energy intake, whether snacking plays an “essential” or “excessive” role in children’s diets is an important nutritional consideration, particularly for young children for whom snacks are believed to have most nutritional relevance for growth and development [4].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the following works have tried to clarify the possible implication of this MC4R SNP in feeding behavior: Stutzmann et al revealed an excessive appetite in a large cohort of European populations, especially eating a large amount of food during meals with a higher frequency of snacking in children and teenagers carriers of this SNP, and a greater hunger in adults carriers of the same polymorphism [ 143 ]. Snacking is a particular dietary pattern, principally during childhood, in which energy-dense and nutrient-poor food is consumed between meals exhibiting a recurrent “snack episode”, which can be translated into a bad feeding style and a risk factor for altered eating behavior and elevated BMI [ 145 , 146 ].…”
Section: Melanocortin Receptors In Feedingmentioning
confidence: 99%